تحسين خصائص الهوائي البوقي بإضافة مواد عازلة - العلي علي (Latakia University Journal -Engineering Sciences Series, 2019)
يقدم هذا البحث دراسة نظرية وعملية لتحسين خصائص الهوائي البوقي الهرمي بإضافة مواد عازلة على فتحته. إن الغاية من هذه الدراسة هي الإجابة على السؤال التالي:هل تؤثر المواد العازلة على المخطط الإشعاعي والربح والاتجاهية؟ وهل يختلف هذا التأثير باختلاف ثابت العازلية الكهربائي النسبي (rε) ؟ تمت الإجابة على هذا السؤال من خلال تصنيع وإضافة مواد عازلة مختلفة القيمة لثابت العازلية الكهربائي (rε) على شكل قطع مكافئ ولصقها على فتحة الهوائي البوقي. إن استخدام طريقة الفروقات المنتهية بالزمن (FDTD)لإجراء التحليل الرياضي اللازم ,أظهرت أن إضافة المواد العازلة يؤثر على التوزع الصفحي وعلى الاستطاعة عند فتحة البوق , مما يؤدي إلى نقصان في اتساع الفص الرئيسي للإشعاع ونقصان في مستوى الفصوص الثانوية , ولكن مع زيادة في قيمة الاتجاهية . بالإضافة لذلك تم إجراء الاختبارات العملية قبل وبعد إضافة المواد العازلة على فتحة الهوائي البوقي, وجرت مقارنها مع نتائج طريقة (FDTD). This research represents theoretical and practical as well as study about the effect of dielectric materials on horn antenna properties. The aim of this study is answering the following questions. Do the dielectric materials affect the radiation pattern, the directivity and gin? Does this effect differ according to the relative dielectric constant. This questions are answered by dielectric materials of different value of the relative dielectric constant on parabolic shape and pasting it on the aperture of the horn antenna . Using differentiating way ending in time (FDTD) to make the necessary mathematical analysis shows that adding the dielectric materials affects thephase and power distribution on the aperture of the horn.This leads to reducing the width of main lobes of the radiation and reducing the level of side lobes, but increasing the level of directivity. In addition ,practical experiments are done before and after adding the dielectric materials on the aperture of the horn antenna and they are compared to the results of (FDTD) method.